THE LEVEL OF PRO-INFLAMMATORY AND ANTI-INFLAMMATORY INTERLEUKINES IN CHILDREN WITH ACUTE BRONCHIOLITIS - Azimova Kamola Talatovna; Haitova Rayhona (Web of Journals Publishing, 2025)
Currently, information about the characteristics of the immune response depending on the severity of acute bronchiolitis in young children is still not fully studied and contradictory. Studies are devoted to studying the activity of interleukins in acute bronchiolitis depending on the severity of the disease. The results obtained will make it possible to clarify the basic mechanisms of the occurrence and course of the inflammatory response in the mucous membranes of the bronchial tree and will make it possible to consider them as additional markers of inflammation that provide a humoral response.
Keywords: Acute bronchiolitis, children, cytokines.